Pergeseran Wewenang Perum Perhutani KPH Malang Dalam Pengelolaan Cagar Budaya (Studi Kasus: Candi Sumberawan, Singosari) - Santoso, Rizki Andi; Siatiman, Reinhard Valent; Amirulazka, Naufal Itsnain; Mustaqim, Muhammad Azhar Shiroth (Equality : Jurnal Hukum dan Keadilan, 2024)
Sumberawan Temple is one of the cultural heritages in Malang Regency. Located in the middle of a pine forest, the temple is managed by Perum Perhutani KPH Malang. As a cultural heritage, the temple should be managed by the Malang Regency Tourism and Culture Office. However, the status quo shows otherwise, there is an overlap of authority between Perum Perhutani KPH Malang and Disparbud Malang District. The regulation of cultural heritage management in Malang Regency has been regulated in Regent Regulation No. 49/2016 on the Position, Structure, Organization, Duties and Functions, and Work Procedures of the Malang Regency Tourism and Culture Office. The regulation stipulates the authority of the Malang District Tourism and Culture Office to carry out the function of cultural heritage management. The purpose of this study is to determine the authority of Perum Perhutani KPH Malang, the Tourism and Culture Office of Malang Regency, and to compare the authority of the two institutions in managing cultural heritage, as well as to analyze the shift in the function of Perum Perhutani KPH Malang through the regulation a quo. The research method used is normative juridical with analytical materials in the form of primary, secondary, and tertiary legal materials. Primary legal materials used are regulations governing the authority to manage cultural heritage. Then, secondary legal materials used are books, journals, articles, previous research results, and expert opinions. The results showed that there is a conflict of functions and authorities in the management of Sumberawan Temple. The conflict is shown by the management of Sumberawan Temple by Perum Perhutani KPH Malang which juridically has no authority.  Therefore, it is necessary to harmonize regulations related to authority in the management of Sumberawan Temple between Perum Perhutani KPH Malang and Malang Regency Tourism and Culture Office.